Iterative Method for Analysis of Dimmable Self-oscillating Electronic Ballast Under Bus Voltage Control - Maikel F. Menke; Marcelo Freitas da Silva; Álysson R. Seidel; Juliano P. Lopes; Marina S. Perdigão; José M. Alonso (Eletrônica de Potência, 2015)
This paper presents a predictive method of the self-oscillating electronic ballast (SOEB) behavior under dimming conditions. This work is focused on the bus voltage variation dimming method, where a closed analysis is not possible to carry out without considering the interaction among inverter bus voltage, fluorescent lamp power/resistance nonlinear behavior, and frequency operation of the SOEB. Thus, an iterative method is proposed in order to predict the oscillating frequency related with the fluorescent lamp power under bus voltage variation. Experimental results for a T8 32 W fluorescent lamp are obtained in order to compare simulation results, and verify the feasibility of the proposed method